The Correlation between Metacognitive Knowledge with Mathematics Anxiety in the First Grade High School Female Students - Farhad Karimi (Journal of Global Pharma Technology, 2017)
The aim of this study was to investigate the relationship between control source and role-personality conflict the purpose of this study is to investigate the correlation between met cognitive knowledge and math anxiety. The population of the study consists of 1950 female students in the first grade of high school in Tehran 8th district. 323 female students were selected using cluster sampling. The instrument consisted of two standardized questionnaires designed by Swanson to assess problem-solving met cognitive knowledge and Math Anxiety Scale constructed by Chiu and Henry. Using factor analysis and Cranach’s alpha, both validity and reliability of the questionnaires were attained. Analyzing the data in the descriptive statistics area was conducted by frequency and percentage and in inferential statistics with the Pearson correlation showed that the relationship between met cognitive knowledge and problem solving with math anxiety is negatively significant at 99%confidence level (r=-0/454).The relationship between the components of met cognitive knowledge (person, task and strategy) with math anxiety is significantly negative. In other words, the more the learner informed and aware of the cognitive system, task, and strategy, the less he/she will feel math anxiety. The index of knowledge of strategies demonstrates the most significant negative relationship with students' math anxiety while the two other indexes, knowledge of self and task, are in the next levels respectively. The results generally indicate that more students are aware of problem-solving met cognitive knowledge, less they suffer from math anxiety.Keywords: Math Anxiety, Met cognitive knowledge, The first grade high school.